Unlocking the therapeutic potential of thymus-isolated regulatory T cells - Hu, Yueyuan; Cruz, Hugo; Santosh Nirmala, Samikshya; Fuchs, Anke (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) play a pivotal role in modulating excessive immune responses and maintaining immune homeostasis in humans. Notably, therapeutic strategies employing autologous and allogeneic Tregs have shown promising signs of efficacy in the treatment and prevention of graft versus-host disease (GvHD), transplant rejection and autoimmune diseases. Treg cells are typically obtained from peripheral blood or umbilical cord blood, but the largely antigen-experienced memory state of peripheral blood Tregs and the limited number of Tregs that can be isolated from cord blood remain obstacles. However, recent studies have identified the thymus as a novel and promising source of Tregs, overcoming the abovementioned limitations. Currently, human thymus-isolated regulatory T cells (thyTregs) are being investigated in phase 1/2 clinical trials to assess their safety and efficacy in both autologous and allogeneic settings. This review provides a comprehensive overview of the different manufacturing processes for isolation and expansion of thymus-derived regulatory T cells, their clinical relevance and current ongoing clinical trials investigating the therapeutic potential of this novel class of Tregs.